Christian Misionaries Responsibilities in Preaching - Rinawaty Rinawaty; Hannas Hannas (Jurnal Didaskalia, 2019)
Preaching the Word of God or sermonizing is God's commandment which must be done by every believer. Missionaries are people who are specifically called to convey the truth of the Word of God, through sermons, Bible study and living testimonies that glorify God. Missionaries experience obstacles in preaching because of many factors, such as: lack of mastery in hermeneutic and homiletical skills and ignoring the communication skill. Therefore the text assessment will be shallow and its relevance at the present time has not been well delivered. Those limitations must be the missionaries’ main concern besides spiritual qualifications that are equally important. The research found several important things, such as: the right definition for Christian missionaries, Christian missionaries’ responsibilities and Christian missionaries’ preaching in the perspective of a communication skill. This research was conducted in qualitative methods that provide descriptions and histories with social sciences, theology, communication approaches.